2007
DOI: 10.1016/j.brainres.2006.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinases regulate glycine receptor binding in brain stem auditory nuclei after unilateral cochlear ablation

Abstract: Glycinergic synaptic inhibition is part of acoustic information processing in brain stem auditory pathways and contributes to the regulation of neuronal excitation. We found previously that unilateral cochlear ablation (UCA) in young adult guinea pigs decreased [ 3 H]strychnine binding activity in several brain stem auditory nuclei. This study determined if the UCA-induced deficit could be regulated by protein kinase C (PKC), protein kinase A (PKA) or Ca 2+ /calmodulin-dependent protein kinase II (CaMKII). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Efflux rate constants (910 -3 min -1 ) ± SEM k 1 k 2 k 2 (50 mM K + ) Basal (control) 3.64 ± 0.14 [41] 3.15 ± 0.12 [16] 6.84 ± 0.33 [16] t-ACPD 3.70 ± 0.24 [8] 3.30 ± 0.20 [4] 6.08 ± 0.67 [4] DHPG 4.72 ± 0.37** [8] 3.89 ± 0.08** [4] 7.35 ± 0.73 [8] + AIDA 3.91 ± 0.07 [4] 3.13 ± 0.14* [4] 7.52 ± 0.42 [6] 2R,4R-APDC 3.81 ± 0.29 [8] 2.95 ± 0.16 [4] 8.10 ± 0.62 [4] L-AP4 3.96 ± 0.33 [7] 3.10 ± 0.40 [4] 6.94 ± 0.38 [4] L-SOP 4.77 ± 0.29** [8] 3.74 ± 0.39** [4] 10.52 ± 1.12** [4] + CPPG 3.36 ± 0.32*** [4] 3.00 ± 0.18 [4] 6.03 ± 0.48 [12] AIDA 3.80 ± 0.26 [8] 3.42 ± 0.29 [4] 6.41 ± 0.37 [4] CPPG 3.88 ± 0.20 [8] 3.29 ± 0.31 [4] 6.07 ± 0.61 [4] The slices were preloaded for 30 min with 10 lM stimulatory effect of glycine further confirms the involvement of transporters in the release. In Na + -free media the transporters were not functional, and accordingly, addition of extracellular glycine caused no effect.…”
Section: Role Of Transportersmentioning
confidence: 98%
See 2 more Smart Citations
“…Efflux rate constants (910 -3 min -1 ) ± SEM k 1 k 2 k 2 (50 mM K + ) Basal (control) 3.64 ± 0.14 [41] 3.15 ± 0.12 [16] 6.84 ± 0.33 [16] t-ACPD 3.70 ± 0.24 [8] 3.30 ± 0.20 [4] 6.08 ± 0.67 [4] DHPG 4.72 ± 0.37** [8] 3.89 ± 0.08** [4] 7.35 ± 0.73 [8] + AIDA 3.91 ± 0.07 [4] 3.13 ± 0.14* [4] 7.52 ± 0.42 [6] 2R,4R-APDC 3.81 ± 0.29 [8] 2.95 ± 0.16 [4] 8.10 ± 0.62 [4] L-AP4 3.96 ± 0.33 [7] 3.10 ± 0.40 [4] 6.94 ± 0.38 [4] L-SOP 4.77 ± 0.29** [8] 3.74 ± 0.39** [4] 10.52 ± 1.12** [4] + CPPG 3.36 ± 0.32*** [4] 3.00 ± 0.18 [4] 6.03 ± 0.48 [12] AIDA 3.80 ± 0.26 [8] 3.42 ± 0.29 [4] 6.41 ± 0.37 [4] CPPG 3.88 ± 0.20 [8] 3.29 ± 0.31 [4] 6.07 ± 0.61 [4] The slices were preloaded for 30 min with 10 lM stimulatory effect of glycine further confirms the involvement of transporters in the release. In Na + -free media the transporters were not functional, and accordingly, addition of extracellular glycine caused no effect.…”
Section: Role Of Transportersmentioning
confidence: 98%
“…Table 1 Effects of ion channel inhibitors and compounds involved in the second messenger systems on glycine release from mouse brain stem slices Concentration (mM) Efflux rate constants (910 -3 min -1 ) ± SEM k 1 k 2 k 2 (50 mM K + ) Basal (control) 3.64 ± 0.14 [41] 3.15 ± 0.12 [16] 6.84 ± 0.33 [16] DIDS 0.5 3.62 ± 0.13 [22] 3.11 ± 0.14 [11] 6.73 ± 0.57 [11] SITS 2.0 3.02 ± 0.25* [16] 2.44 ± 0.29* [8] 6.69 ± 0.32 [8] 9-AC 0. 2 3.23 ± 0.20 [8] 2.67 ± 0.14 [4] 5.37 ± 0.40 [4] Riluzole 0.1 3.35 ± 0.22 [11] 2.75 ± 0.29 [4] 4.86 ± 0.70** [7] Genistein 0.001 3.41 ± 0.25 [16] 3.00 ± 0.17 [8] 4.11 ± 0.40** [7] Quinacrine The drugs were added at the beginning of the superfusion and 50 mM K + at 30 min. The results show the efflux rate constants ± SEM (910 -3 min -1 ) for the time intervals of 20-30 min (k 1 ) and for 32-40 min (k 2 ) with the number of independent experiments in parenthesis.…”
Section: Ion Channel Blockersmentioning
confidence: 98%
See 1 more Smart Citation
“…Downstream events of such factor(s) could at least imply protein kinase activity. In that respect, it has been shown that, in the retina and in auditory nuclei, protein kinases modulate strychnine binding and, hence, GlyR expression (Salceda and Aguirre-Ramirez, 2005 ; Yan et al, 2007 ). Figure 1 summarizes the current findings on glycine and GlyR signalling in macroglial cells.…”
Section: Neuroglial Cellsmentioning
confidence: 99%
“…Conformational changes induced by phosphorylation were delineated, , and phosphorylation was shown to affect the kinetics of GlyR channel activation and desensitization ,, as well as current amplitudes and single-channel conductance of recombinant GlyRs expressed in Xenopus oocytes. Phosphorylation-dependent changes on receptor surface expression and internalization ,,, and motility in the membrane were described. Phosphorylation modulates ethanol sensitivity of GlyRs and GlyR-mediated nociceptive signaling. , Aspects of GlyR phosphorylation have been discussed and reviewed in detail. ,,,,, …”
Section: Modulators Of the Inhibitory Glycine Receptormentioning
confidence: 99%